Reframing rhetorical history : cases, theories, and methodologies - Turner, Kathleen J., 1952-; Black, Jason Edward (Tuscaloosa : The University of Alabama Press, 2022)
"Reframing Rhetorical History both reassesses history as rhetoric and rhetorical history as practice. It attends to a number of topics that have become not just "hot button" issues in rhetorical scholarship over the ensuing two decades, but which have entrenched themselves as anchors within the field, among them digital rhetoric, public memory, race and ethnicity, gender dynamics and sexualities, dis/abilities, health and well-being, environmentalism, transnationalism and globalization, social justice, archival methods and archival politics, performance theory, and colonialism and decoloniality. The sixteen essays are divided into four major parts. "Digital Humanities and Culture" introduces methods and cases involving 21st century technologies; the chapters here address the profundity, utility, and limitations of data science, digital archiving, and social media in both gathering rhetorical-historical texts and analyzing them as a method. "Subject Positionality, Culture, and Archives" addresses race and gender within the contexts of critical race theory, gendered health rhetoric, race-based public memory, and class/sectionalism. It also offers fresh perspectives on the nature of archives, positing them less as stagnant, dusty repositories and more as sources of power-laden ideas and living and breathing bodies of resistive agency. The third section explores post-9/11 ideologies related to U.S. and international cultures. Titled "Approaches to Nationalism and Transnationalism," this collection of chapters explores nationalistic fervor and fragility in cases of colonial states, border politics, citizenship, legal imperialism, and remembering. The fourth section, "Recovery of Rhetorical History in the Corpus and Classroom" explores creative ways to recover history given what the field has learned since the publication of Doing Rhetorical History. Cases here aim to retrieve lost rhetorical-historical documents and to work the study of rhetorical history into 21st century classrooms"--
"Collection of essays that reassesses history as rhetoric and rhetorical history as practice "--
Introduction: The doing and reframing of rhetorical history / Jason Edward Black -- #leelah alcorn : trans*-ing rhetorical history in the digital humanities lab / Joe Edward Hatfield -- Rhetorical history, the public humanities, and the exoduster movement / Shawn J. Parry-Giles and J. Michael Hogan -- Martin Luther King Jr. in East Berlin : prophetic history and the convergence of codes from the sermonic to the king-code / Christopher J. Oldenburg and Adrienne E. Hacker Daniels -- Visually based rhetorical history : the Sola Vidēre Principle in Christian nationalist videos / Philip Perdue -- Doing rhetorical history with Ralph Ellison : meta-archival meditations on the present, via the past / Bryan Crable -- Negotiating public scientific regulatory controversies : Dr. Frances O. Kelsey's productive postponement of Thalidomide in the United States / Madison A. Krall -- "To wake up the latent powers" : the rhetoric of Henry McNeal Turner and the legacy of the Israel AME Lyceum / Andre E. Johnson -- Crucial intersections : public memories and/as rhetorical history / Roseann M. Mandziuk -- Decolonizing rhetorical history / Matthew deTar -- Forgetting or remembering the nation? Amnesic rhetoric and circulation of the past / Chandra A. Maldonado -- The greatest hero of the Great War : Alvin C. York as a rhetorical construction / Daniel P. Overton -- Writing the sovereign citizen in Cold War era expatriation law : a rhetorical history of Yaser Hamdi's Settlement agreement (2004) / Margaret Franz -- The Frankfurt anecdote and rhetorical history : toward a method for reading National Security Archives / Andrew D. Barnes -- Reading the Logos in Hebrew : a provocation for rethinking through rhetorical history / Lisbeth A. Lipari -- A rhetorical history of southern rhetoric / Christina L. Moss -- Knowledge, rhetorical history, and undergraduate scholars : reimagining liberal education / Sean Patrick O'Rourke and Melody Lehn.
Description based on print version record.
Includes bibliographical references (pages 359-407) and index.
eBooks on EBSCOhost
Keywords: Speeches, addresses, etc., American -- History and criticism; Communication in politics -- United States -- History -- Case studies; English language -- United States -- Rhetoric -- Case studies; Rhetoric -- Political aspects -- United States -- History -- Case studies; Rhetoric -- Social aspects -- United States -- History -- Case studies; United States -- Historiography; Discours américains -- Histoire et critique; Communication politique -- États-Unis -- Histoire -- Études de cas; Anglais (Langue) -- États-Unis -- Rhétorique -- Études de cas; Discours politique -- États-Unis -- Histoire -- Études de cas; Rhétorique -- Aspect social -- États-Unis -- Histoire -- Études de cas; LANGUAGE ARTS & DISCIPLINES / Rhetoric; LANGUAGE ARTS & DISCIPLINES / Communication Studies; Speeches, addresses, etc., American; Rhetoric -- Social aspects; Rhetoric -- Political aspects; Historiography; English language -- Rhetoric; Communication in politics; United States; History; Criticism, interpretation, etc; Case studies